Pioduran National High School (PDNHS) library development plan - Bachiller, Ross T. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
Before the start of the project, Pioduran National High School (PDNHS) has a library that is not properly organized that would answer the information needs of its students and teachers. The reorganization of the PDNHS Library will be helpful in the instilling the importance of education and literacy to the students of PDNHS.